Inventarisasi Dan Karakterisasi Famili Poaceae Di Cibiru Hilir, Cileunyi, Kabupaten Bandung - Syifa Raisatul Azkia; Syifa Ripatul Aliyah; Ateng Supriatna (Student Scientific Creativity Journal, 2023)
Poaceae which is characterized by woody stems, segmented reeds, with a hollow book in the middle, yellow, green or purple outer skin. Young stems are always covered with a very tight sheath, hairy brown or blackish, the sheath will fall off as the length of the stem grows. Plant inventory aims to determine the potential and benefits of a plant so that it can be used as a literature study for everyone. There are 4 species of plants found in Cibiru Hilir, namely lemongrass, rice, love grass, and bamboo trees. The morphological identification carried out can be seen through individual observations which are then compared with the literature.